Multiple roles and regulatory mechanisms of the transcription factor HNF4 in the intestine - Vemuri, Kiranmayi; Radi, Sarah H.; Sladek, Frances M.; Verzi, Michael P. (Frontiers in Endocrinology, 2023)
Hepatocyte nuclear factor 4-alpha (HNF4α) drives a complex array of transcriptional programs across multiple organs. Beyond its previously documented function in the liver, HNF4α has crucial roles in the kidney, intestine, and pancreas. In the intestine, a multitude of functions have been attributed to HNF4 and its accessory transcription factors, including but not limited to, intestinal maturation, differentiation, regeneration, and stem cell renewal. Functional redundancy between HNF4α and its intestine-restricted paralog HNF4γ, and co-regulation with other transcription factors drive these functions. Dysregulated expression of HNF4 results in a wide range of disease manifestations, including the development of a chronic inflammatory state in the intestine. In this review, we focus on the multiple molecular mechanisms of HNF4 in the intestine and explore translational opportunities. We aim to introduce new perspectives in understanding intestinal genetics and the complexity of gastrointestinal disorders through the lens of HNF4 transcription factors.